Neonatal and maternal outcomes of mRNA versus Non-mRNA COVID-19 vaccines in pregnant patients: a systematic review and meta-analysis - Oliveira J. A.; da Silva E. G.; GÖKMEN KARASU A. F.; Silva A. M. N.; Philip C. E. (My University, 2024)
Objective: To compare the effectiveness and safety of non-mRNA versus mRNA COVID-19 vaccines on pregnant women and their newborns in a systematic review with meta-analysis. Data sources: We searched PubMed, Embase, and Cochrane Central in May 2023. Study selection: The search strategy yielded 4451 results, 16 studies were fully reviewed. We selected case-control studies analysing non-mRNA versus mRNA vaccines. Data collection and analysis: we assessed the risk of bias using the Cochrane Risk of Bias in Nonrandomized Studies of Interventions [ROBINS-I] tool. Standardised mean differences were pooled using random-effect models. Data synthesis: We identified 8 prospective and retrospective studies with a total of 32,153 patients. Non-mRNA vaccines were associated with a higher incidence of fever [OR 2.67; 95% CI 2.08-3.43; p<0.001], and a lower incidence of fetal or neonatal death [OR 0.16; 95% CI 0.08-0.33; p<0.001]. In subgroup analyses, the Jansen vaccine [Ad26.COV2.S] was found to have a higher rate of premature labor/delivery [OR 4.48; 95% CI 1.45-13.83; p=0.009] and missed/spontaneous abortion [OR 1.90; 95% CI 1.09-3.30; p=0.02], as compared with the Pfizer [BNT162b2] vaccine. Conclusion: non-mRNA vaccines are associated with a lower incidence of fetal or neonatal death among pregnant women who receive a Covid19 vaccine, although at an increased rate of pyrexia compared with mRNA vaccines. Other studies are required for better assessment.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Obstetrics and Gynecology; Health Sciences; Kadın Hastalıkları & Doğum; Klinik Tıp; Klinik Tıp (Med); Obstetrics & Gynecology; Clinical Medicine; Clinical Medicine (Med); Doğum ve Jinekoloji